2008
DOI: 10.1007/s10811-008-9321-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the heterosis of Laminaria hybrids with the genetic distance between their parental gametophyte clones

Abstract: Eighteen microsatellite markers were used to determine the genetic distances between the parental gametophyte clones of 14 Laminaria hybrids, which were then used to establish a linear relationship with the heterosis (hybrid vigor) of economic traits including yield, mean blade try weight, mean blade fresh weight, blade length, blade width and mean blade thickness using regression analysis. Significant regression was found between the genetic distance (x) and the heterosis (y) of yield (y=115.10x−77.97, r=0.81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…The superiority of some of our inter-cultivar hybrids (Table 2, Figs. 2 and 3) compares well with crossing products of commercial L. japonica clones described by Li et al (2008). Furthermore, our observations include cases of hybrid depression and reciprocal asymmetry (Table 2; Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The superiority of some of our inter-cultivar hybrids (Table 2, Figs. 2 and 3) compares well with crossing products of commercial L. japonica clones described by Li et al (2008). Furthermore, our observations include cases of hybrid depression and reciprocal asymmetry (Table 2; Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Due to the dominant diploid state combined with obligatory sexual reproduction and dioecism, the occurrence of heterosis in kelps is not surprising, and a first case has been reported for Undaria by Hara and Akiyama (1985). Heterosis breeding strategies are presently applied in Laminaria mariculture in China, using intraspecific matings between Laminaria japonica cultivars (Li et al 2008) and reciprocal crosses between cultivars of L. japonica and L. longissima (Li et al 2007;Zhang et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in species of Saccharina. Li et al (2008b) found a significant relationship between the genetic distance of parental Laminaria (Saccharina) gametophyte clones measured using microsatellite markers and heterosis of agronomical traits of the first filial hybrids. All of these investigations have indicated that genetic distance between parental individuals, computed based on molecular markers such as microsatellites, AFLP and others, could be used to estimate the heterosis of their hybrids.…”
Section: Introductionmentioning
confidence: 93%
“…Precise prediction of the hybrid performance or heterosis before performing hybridization experiments enhances the efficiency of the breeding process. Such investigations have been conducted in the guppy, maize and Saccharina species (Shikano and Taniguchi, 2002;Kiula et al, 2008;Li et al, 2008b). Shikano and Taniguchi (2002) revealed that genetic distance measured by molecular markers positively correlated with the degree of heterosis in guppies (Poecilia reticulata).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, closely related Laminaria species were crossed in order to produce superior genotypes in China Li et al 2007). Li et al (2008) used molecular techniques to correlate genetic distances between Lami naria parent lines and economically interesting characters of their heterosis products. Our results show that Macro cystis will now be a new candidate, offering the potential of heterosis breeding in another economically interesting kelp species.…”
Section: Heterosis In Agricultural Crops and Kelpsmentioning
confidence: 99%